Flexible graphite bipolar plate for fuel cell and preparation method of flexible graphite bipolar plate

Through strong acid etching and high-temperature treatment, combined with vacuum and positive pressure immersion processes, the small and medium pore problems of flexible graphite bipolar plates are solved, the resin filling rate and plate performance are improved, and the airtightness and physical strength are achieved to meet the fuel Efficient working requirements for batteries.

CN119191877APending Publication Date: 2024-12-27ZHEJIANG TIANNENG HYDROGEN ENERGY TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411159642.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-21
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing flexible graphite bipolar plates have pore problems of less than 0.1μm during the preparation process, which affects their airtightness and physical strength, resulting in low resin filling rate and cannot meet the efficient working requirements of fuel cells.

Method used

The prefabricated plate is treated with strong acid etching to regulate the pore distribution and size, improve the hydrophilicity of the electrode plate through doping of oxygen-containing groups, enhance the resin wetting ability, and improve the resin filling rate through high-temperature calcination and vacuum and positive pressure immersion processes.

Benefits of technology

The number of pores less than 0.1 μm is significantly reduced, the resin filling rate is improved, the airtightness and physical strength of the flexible graphite bipolar plate are enhanced, and its performance in fuel cells is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119191877A_ABST
    Figure CN119191877A_ABST
Patent Text Reader

Abstract

The invention discloses a flexible graphite bipolar plate for a fuel cell and a preparation method of the flexible graphite bipolar plate, and relates to the field of fuel cell bipolar plates. According to the method, strong acid etching is combined with high-temperature treatment, so that the content of pores smaller than 0.1 mu m in the prefabricated slab is reduced; the hydrophilic performance of the prefabricated plate is enhanced by adding oxygen-containing functional groups, so that the wettability of mixed resin and the prefabricated plate is improved, the filling rate of the resin in the prefabricated plate is improved by enhancing the flowability of the resin under the same operation condition, and then the air tightness and physical strength of the finished graphite plate are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of fuel cell bipolar plates, and in particular to a flexible graphite bipolar plate for a fuel cell and a preparation method thereof. Background Art

[0002] Proton exchange membrane fuel cell is a power generation device that directly converts the chemical energy in fuel and oxidant into electrical energy. It has become the focus of fuel cell research and development due to its good high-current discharge. It has the advantages of high power density, low operating temperature and no pollution of reaction products. Bipolar plate is a key component in proton exchange membrane fuel cell. It plays many important roles in fuel cell, such as supporting membrane electrode structure, separating hydrogen and oxygen, collecting current, conducting heat, discharging water generated by reaction and preventing gas and coolant leakage.

[0003] At present, the main materials of bipolar plates are metal bipolar plates, graphite bipolar plates and composite graphite bipolar plates. Metal bipolar plates have excellent mechanical stability, electrical and thermal conductivity, and good gas sealing, but they have corrosion problems, and their surface requires further protective coating process, which increases their cost; the complex preparation process of graphite bipolar plates leads to high costs, and their performance is relatively brittle; graphite and resin-based composite materials can improve their corrosion resistance and conductivity, and the preparation process is simple, so they are widely used in proton exchange membrane fuel cell bipolar plates.

[0004] The patent application with publication number CN117423842A discloses a method for preparing a flexible graphite / resin bipolar plate, comprising the following steps: mixing a biomass material with a phosphide, adding deionized water and standing, drying after standing, further phosphating, mixing the product obtained after the phosphating with a silicon dioxide catalyst for carbonization, and washing to obtain biomass graphite; mixing the biomass graphite with ethanol and ball milling, collecting the product after ball milling and drying to obtain flexible graphite powder; pressing the flexible graphite powder into a flexible graphite material plate, and molding the flexible graphite material plate to obtain a flexible graphite bipolar plate; vacuum impregnating the flexible graphite bipolar plate with resin, washing and drying after impregnation, further molding, and heating after molding to obtain a flexible graphite / resin bipolar plate.

[0005] The patent application with publication number CN114559579A discloses a high-density flexible graphite bipolar plate and its preparation method and application. The flexible expanded graphite is mixed and pre-treated with a low-viscosity dilute resin solution, and the resin is impregnated after the molding process to make the resin evenly distributed inside the flexible graphite bipolar plate, effectively reducing the porosity inside the bipolar plate, improving the physical strength and air tightness of the bipolar plate, and finally obtaining a high-density flexible graphite bipolar plate, thereby improving the working efficiency and service life of the fuel cell.

[0006] In the process of preparing flexible graphite plates, a press is used to press the expanded graphite prefabricated plate into the required process prefabricated plate, and then the air tightness and physical strength are improved by resin impregnation. Therefore, it is a key process to ensure that the resin fully fills the pores of the prefabricated plate and fully solidifies. In the process of pressing the prefabricated plate, due to problems such as the uniformity of the dispersion of the worm graphite powder and the pressing process, the prefabricated plate will have graphite pores of different sizes, accompanied by a certain amount of pores less than 0.1μm. Due to the high viscosity of the resin, small pores are not conducive to the filling of the resin, which in turn affects the air tightness and physical strength of the bipolar plate. Therefore, it is very important to eliminate pores less than 0.1μm as much as possible and increase the filling rate of the resin for the preparation of flexible graphite bipolar plates. Summary of the invention

[0007] Based on the deficiencies in the prior art, the present invention uses a strong acid to pretreat the prefabricated plate after pressing, regulates its pore distribution and size through the etching effect of the acid, and reduces the number of pores less than 0.1 μm through the collapse of the pores; at the same time, the hydrophilicity of the plate is improved by doping with oxygen-containing groups, thereby improving the wettability of the resin to enhance the filling of the plate pores by the resin, thereby improving the air tightness and physical strength of the flexible graphite bipolar plate.

[0008] The present invention is achieved through the following technical solutions:

[0009] The present invention also provides a method for preparing a flexible graphite bipolar plate for a fuel cell, comprising the following steps:

[0010] (1) pressing the expanded graphite plate to obtain a prefabricated plate with a flow field, and then placing it in an oxygen-containing acid and etching it under heating conditions;

[0011] (2) cleaning and drying the prefabricated plate after etching in step (1), and then calcining it at high temperature in an inert atmosphere;

[0012] (3) The prefabricated plate calcined at high temperature in step (2) is subjected to vacuum degassing, negative pressure impregnation, positive pressure impregnation, cleaning and drying to obtain the flexible graphite bipolar plate for fuel cell.

[0013] Preferably, in some embodiments of the present invention, in step (1), the expanded graphite sheet is purchased from Ningbo Xinyuan Industrial Group, and the surface density is 50-70 g / cm 2 ;

[0014] The oxygen-containing acid used in the present invention is selected from phosphoric acid and nitric acid, which are commonly used etching acids and contain more oxygen groups, and can enhance the hydrophilicity of the prefabricated board; wherein the phosphoric acid is a phosphoric acid aqueous solution with a mass fraction of 5-20wt%, and the nitric acid is a nitric acid aqueous solution with a mass fraction of 5-20wt%;

[0015] The mass ratio of the phosphoric acid aqueous solution to the nitric acid aqueous solution is 5-20:1.

[0016] Preferably, the mass ratio of the prefabricated board to the oxygen-containing acid is 1:50-220;

[0017] The etching process parameters are: etching process at a temperature of 70-90° C. for 24-48 hours.

[0018] At a higher temperature (80° C. is selected as an example in the embodiment of the present invention), etching is more likely to occur, thereby changing the structure of the pores.

[0019] In some embodiments of the present invention, in step (2), the drying temperature is 80-120° C. and the drying time is 12-48 h;

[0020] The inert gas is high-purity nitrogen or argon, and the flow rate is 50-200 ml / min.

[0021] The high temperature calcination temperature is 600-950°C and the time is 3-12h.

[0022] In some embodiments of the present invention, in step (3), the pressure of the negative pressure immersion is -80 to -95 KPa, and the maintenance time is 3 to 9 hours;

[0023] The positive pressure impregnation pressure is 400Kpa-800Kpa, and the impregnation time is 6-12h.

[0024] Negative pressure impregnation can remove residual air and moisture in the pores of the prefabricated board; positive pressure impregnation can then better penetrate the resin into the pores of the prefabricated board.

[0025] Further, during impregnation, the prefabricated board is placed in a resin, a curing agent and an initiator;

[0026] The resin, curing agent and initiator can all be commercially available products. In the embodiments of the present invention, the resin is Heneng 994 commercial resin, the curing agent is 2,2′-azobis(2,4-dimethylvaleronitrile), and the accelerator is azobisisobutyronitrile as an example.

[0027] The mass ratio of the resin, the curing agent and the initiator is 1000:2:2.

[0028] Specifically, the cleaning and drying includes organic solvent cleaning, water bath curing and high temperature leveling;

[0029] The organic solvent used in the organic solvent cleaning is one of ethanol and isopropanol, and the cleaning time is 5-30 minutes, followed by cleaning with deionized water;

[0030] The water bath curing temperature is 85-95°C and the curing time is 1-4h;

[0031] The steps of high temperature leveling are: first drying at a temperature of 100-150° C. for 0.5-3 hours, and then high temperature leveling at a temperature of 150-200° C. for 1-10 minutes.

[0032] The present invention also provides a flexible graphite bipolar plate for a fuel cell prepared by the preparation method.

[0033] Beneficial effects of the present invention:

[0034] The present invention reduces the content of pores smaller than 0.1 μm in the prefabricated plate by combining strong acid etching with high temperature treatment; enhances the hydrophilicity of the prefabricated plate by adding oxygen-containing functional groups, thereby improving the wettability of the mixed resin and the prefabricated plate; and under the same operating conditions, increases the filling rate of the resin in the prefabricated plate by enhancing the fluidity of the resin, thereby improving the air tightness and physical strength of the finished graphite plate. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 It is a graph of airtightness test data of Examples 1-6 and Comparative Example 1.

[0036] Figure 2 It is a bending test data chart of Examples 1-6 and Comparative Example 1. DETAILED DESCRIPTION

[0037] The expanded graphite plates used in the embodiments of the present invention and the comparative examples were purchased from Ningbo Xinyuan Industrial Group. The surface density in the experiment was 70 g / cm2, and the mass of a single plate was about 30 g. The curing resin was the purchased Heneng HPS994, the curing agent was 2,2′-azobis(2,4-dimethylvaleronitrile) (Vazo52), and the initiator was azobisisobutyronitrile (Vazo64). The mass ratio of the resin to the curing agent and the initiator was 1000:2:2. After being evenly mixed and dispersed, they were used as an impregnation liquid.

[0038] Example 1

[0039] Select 2 pieces of 70g / cm 2The surface density hydrogen plate expanded graphite is pressed by a press and then washed with clean water, then placed in a storage basket, 6000g of 10wt% phosphoric acid and 1200g of 10wt% nitric acid are added, and the cover is etched at 80°C for 24h. The etched prefabricated plate is washed with clean water for several times, and then placed in an air drying oven and dried at 100°C for 24 hours; then the prefabricated plate is placed in a high-temperature calcining furnace, 100ml / min of high-purity nitrogen is introduced, and then heat-treated at 700°C for 6 hours; then the prefabricated plate is transferred to the plate impregnation production line, the prepared impregnation solution is added, vacuumed to -95Kpa, maintained for 6 hours, and then a positive pressure of 600Kpa is applied to it, and the maintenance time is 9 hours; after the impregnation is completed, it is drained at room temperature for 30 minutes, and then the residual resin on the surface is cleaned with an ethanol cleaning agent for 15 minutes; then the prefabricated plate is transferred to a water bath environment, cured and dried at 90°C for 3 hours, and then dried at 125°C in an air drying oven for 1 hour, and finally high-temperature leveling is performed at 175°C for 3 minutes to obtain the required graphite plate.

[0040] Example 2

[0041] Select 2 pieces of 70g / cm 2 The surface density hydrogen plate expanded graphite is pressed by a press and then washed with clean water, then placed in a storage basket, 6000g of 10wt% phosphoric acid and 600g of 10wt% nitric acid are added, and the cover is etched at 80°C for 24h. The etched prefabricated plate is washed with clean water for several times, and then placed in an air drying oven and dried at 100°C for 24 hours; then the prefabricated plate is placed in a high-temperature calcining furnace, 100ml / min of high-purity nitrogen is introduced, and then heat-treated at 700°C for 6 hours; then the prefabricated plate is transferred to the plate impregnation production line, the prepared impregnation solution is added, vacuumed to -95Kpa, maintained for 6 hours, and then a positive pressure of 600Kpa is applied to it, and the maintenance time is 9 hours; after the impregnation is completed, it is drained at room temperature for 30 minutes, and then the residual resin on the surface is cleaned with an ethanol cleaning agent for 15 minutes; then the prefabricated plate is transferred to a water bath environment, cured and dried at 90°C for 3 hours, and then dried at 125°C in an air drying oven for 1 hour, and finally high-temperature leveling is performed at 175°C for 3 minutes to obtain the required graphite plate.

[0042] Example 3

[0043] Select 2 pieces of 70g / cm 2The surface density hydrogen plate expanded graphite is pressed by a press and then washed with clean water, then placed in a storage basket, 6000g of 10wt% phosphoric acid and 300g of 10wt% nitric acid are added, and the cover is etched at 80°C for 24h. The etched prefabricated plate is washed with clean water for several times, and then placed in an air drying oven and dried at 100°C for 24 hours; then the prefabricated plate is placed in a high-temperature calcining furnace, 100ml / min of high-purity nitrogen is introduced, and then heat-treated at 700°C for 6 hours; then the prefabricated plate is transferred to the plate impregnation production line, the prepared impregnation solution is added, vacuumed to -95Kpa, maintained for 6 hours, and then a positive pressure of 600Kpa is applied to it, and the maintenance time is 9 hours; after the impregnation is completed, it is drained at room temperature for 30 minutes, and then the residual resin on the surface is cleaned with an ethanol cleaning agent for 15 minutes; then the prefabricated plate is transferred to a water bath environment, cured and dried at 90°C for 3 hours, and then dried at 125°C in an air drying oven for 1 hour, and finally high-temperature leveling is performed at 175°C for 3 minutes to obtain the required graphite plate.

[0044] Example 4

[0045] Select 2 pieces of 70g / cm 2 The surface density hydrogen plate expanded graphite is pressed by a press and then washed with clean water, then placed in a storage basket, 12000g of 10wt% phosphoric acid and 1200g of 10wt% nitric acid are added, and the cover is etched at 80°C for 24h. The etched prefabricated plate is washed with clean water for several times, and then placed in an air drying oven and dried at 100°C for 24 hours; then the prefabricated plate is placed in a high-temperature calcining furnace, 100ml / min of high-purity nitrogen is introduced, and then heat-treated at 700°C for 6 hours; then the prefabricated plate is transferred to the plate impregnation production line, the prepared impregnation solution is added, vacuumed to -95Kpa, maintained for 6 hours, and then a positive pressure of 600Kpa is applied to it, and the maintenance time is 9 hours; after the impregnation is completed, it is drained at room temperature for 30 minutes, and then the residual resin on the surface is cleaned with an ethanol cleaning agent for 15 minutes; then the prefabricated plate is transferred to a water bath environment, cured and dried at 90°C for 3 hours, and then dried at 125°C in an air drying oven for 1 hour, and finally high-temperature leveling is performed at 175°C for 3 minutes to obtain the required graphite plate.

[0046] Example 5

[0047] Select 2 pieces of 70g / cm 2The surface density hydrogen plate expanded graphite is pressed by a press and then washed with clean water, then placed in a storage basket, 12000g of 10wt% phosphoric acid and 1200g of 10wt% nitric acid are added, and the cover is etched at 80°C for 24h. The etched prefabricated plate is washed with clean water for several times, and then placed in an air drying oven and dried at 100°C for 24 hours; then the prefabricated plate is placed in a high-temperature calcining furnace, 100ml / min of high-purity nitrogen is introduced, and then heat-treated at 900°C for 6 hours; then the prefabricated plate is transferred to the plate impregnation production line, the prepared impregnation solution is added, vacuumed to -95Kpa, maintained for 6 hours, and then a positive pressure of 600Kpa is applied to it, and the maintenance time is 9 hours; after the impregnation is completed, it is drained at room temperature for 30 minutes, and then the residual resin on the surface is cleaned with an ethanol cleaning agent for 15 minutes; then the prefabricated plate is transferred to a water bath environment, cured and dried at 90°C for 3 hours, and then dried at 125°C in an air drying oven for 1 hour, and finally high-temperature leveling is performed at 175°C for 3 minutes to obtain the required graphite plate.

[0048] Example 6

[0049] Select 2 pieces of 70g / cm 2 The surface density hydrogen plate expanded graphite is pressed by a press and then washed with clean water, then placed in a storage basket, 12000g of 10wt% phosphoric acid and 1200g of 10wt% nitric acid are added, and the cover is etched at 80°C for 48h. The etched prefabricated plate is washed with clean water for several times, and then placed in an air drying oven and dried at 100°C for 24 hours; then the prefabricated plate is placed in a high-temperature calcining furnace, 100ml / min of high-purity nitrogen is introduced, and then heat-treated at 700°C for 6 hours; then the prefabricated plate is transferred to the plate impregnation production line, the prepared impregnation solution is added, vacuumed to -95Kpa, maintained for 6 hours, and then a positive pressure of 600Kpa is applied to it, and the maintenance time is 9 hours; after the impregnation is completed, it is drained at room temperature for 30 minutes, and then the residual resin on the surface is cleaned with an ethanol cleaning agent for 15 minutes; then the prefabricated plate is transferred to a water bath environment, cured and dried at 90°C for 3 hours, and then dried at 125°C in an air drying oven for 1 hour, and finally high-temperature leveling is performed at 175°C for 3 minutes to obtain the required graphite plate.

[0050] Comparative Example 1

[0051] Select 2 pieces of 70g / cm 2The surface density hydrogen plate expanded graphite is pressed by a press and then washed with clean water. After drying in an air drying oven at 100°C for 1 hour, it is transferred to the plate impregnation production line, the prepared impregnation solution is added, and it is vacuumed to -95Kpa and maintained for 6 hours, and then a positive pressure of 600Kpa is applied to it and maintained for 9 hours; after the impregnation is completed, it is drained at room temperature for 30 minutes, and then the residual resin on the surface is cleaned with an ethanol cleaning agent for 15 minutes; then the prefabricated plate is transferred to a water bath environment, cured and dried at 90°C for 3 hours, and then dried in an air drying oven at 125°C for 1 hour, and finally high-temperature leveling is performed at 175°C for 3 minutes to obtain the required graphite plate.

[0052] Test Example 1

[0053] The porosity and pore size distribution of the prefabricated board not impregnated with resin, Examples 1-6 and Comparative Example 1 were tested by using a mercury porosimeter. The results are shown in Table 1.

[0054] Table 1 Porosity and pore size distribution test statistics of Examples 1-6 and Comparative Example 1

[0055]

[0056] It can be seen from the test data that when the prefabricated plate is not impregnated with resin, its porosity is relatively large, and there are different numbers of pores in different pore size ranges; after impregnating a certain amount of resin, its porosity decreases significantly, indicating that the resin is successfully filled in the pores of the electrode plate; for Comparative Example 1, its porosity is 15.3%, indicating that there are still a large number of pores in the electrode plate that are not filled with resin, of which pores <0.1μm account for as high as 65.8%, indicating that the resin cannot enter the tiny pores on a large scale under this process, resulting in a larger porosity of the electrode plate; for different embodiments, due to different impregnation process conditions, the pore filling results are different, among which Embodiment 2 has the smallest porosity of 3.1%, and pores <0.1μm account for 35.6%. Compared with other embodiments, the resin is smaller, indicating that the pores <0.1μm can be better filled under this process.

[0057] Test Example 2

[0058] The bipolar plate permeability test of Examples 1-6 and Comparative Example 1 was carried out using a helium mass spectrometer leak detector. The test method is as follows: the plate is pressurized between the upper chamber and the lower chamber to form a sealed environment, the lower chamber is evacuated by a vacuum pump, and helium is filled into the upper chamber to a pressure of 0.35 MPa, and then the vacuum pump is turned off. The helium mass spectrometer continues to evacuate to 5 Pa, the helium flow rate is measured, and the measured value is recorded when the flow rate is stable, and the helium permeability of the plate is calculated. The results are shown in FIG. Figure 1 shown.

[0059] The prefabricated board has a large number of pores, so its air permeability is too large, so it is necessary to use resin to fill the pores to avoid cross-talk between the cathode and the anode during the operation of the electrode; Figure 1 It can be seen that after impregnation with resin, the helium permeability is different under different process conditions. For comparative example 1, since there are still a large number of pores, its helium permeability is relatively large and cannot meet the use requirements of the plate. For examples 1-6, as the porosity decreases, the helium permeability decreases significantly, especially for example 2, whose helium permeability is 1.2×10 -8 / (cm 3 .cm -2 .s -1 ), with better performance.

[0060] Test Example 3

[0061] During the use of bipolar plates, in addition to requiring their air permeability to meet the requirements, due to their skeleton support, they are also required to have a certain physical strength to avoid the occurrence of plate breakage and damage during stacking and use. Therefore, a universal testing machine was used to test the bending strength of the plates of Examples 1-6 and Comparative Example 1. With reference to the bending strength test method for impermeable graphite materials (GB / T13465.2-1992), the three-point bending method was used to test the bending strength of the plates. The results are as follows: Figure 2 shown.

[0062] As can be seen from the figure, different impregnation processes result in different bending strengths; the bending strength of comparative example 1 is 11 MPa, which is the lowest value among the tested samples. This is because there are a large number of pores that are not filled with resin, lacking the filling effect of the cured resin, and the bending strength of the plate is poor; for embodiments 1-6, after a large amount of cured resin is filled into the pores of the plate, the bending strength is significantly improved. The lower the porosity, the more cured resin is filled, which leads to a greater bending strength. For example, embodiment 2 has the best bending strength of 21 MPa.

Claims

1. A method for preparing a flexible graphite bipolar plate for a fuel cell, characterized in that: The following steps are involved: (1) pressing the expanded graphite plate to obtain a prefabricated plate with a flow field, and then placing it in an oxygen-containing acid and etching it under heating conditions; (2) cleaning and drying the prefabricated plate after etching in step (1), and then calcining it at high temperature in an inert atmosphere; (3) The prefabricated plate calcined at high temperature in step (2) is subjected to negative pressure impregnation and positive pressure impregnation, and after cleaning and drying, the flexible graphite bipolar plate for the fuel cell is obtained.

2. The method for preparing a flexible graphite bipolar plate for a fuel cell according to claim 1, characterized in that: In step (1), the surface density of the expanded graphite sheet is 50 to 70 g / cm 2 ; The oxygen-containing acid is phosphoric acid and nitric acid, wherein the phosphoric acid is a phosphoric acid aqueous solution with a mass fraction of 5-20wt%, and the nitric acid is a nitric acid aqueous solution with a mass fraction of 5-20wt%; The mass ratio of the phosphoric acid aqueous solution to the nitric acid aqueous solution is 5-20:

1.

3. The method for preparing a flexible graphite bipolar plate for a fuel cell according to claim 2, characterized in that: The mass ratio of the prefabricated plate to the oxygen-containing acid is 1:50-220; The etching process parameters are: etching process at a temperature of 70-90° C. for 24-48 hours.

4. The method for preparing a flexible graphite bipolar plate for a fuel cell according to claim 1, characterized in that: In step (2), the drying temperature is 80-120° C. and the drying time is 12-48 hours; The inert gas is nitrogen or argon, and the flow rate is 50-200 ml / min. The high temperature calcination temperature is 600-950°C and the time is 3-12h.

5. The method for preparing a flexible graphite bipolar plate for a fuel cell according to claim 1, characterized in that: In step (3), the pressure of the negative pressure immersion is -80 to -95 KPa, and the maintenance time is 3 to 9 hours; The positive pressure impregnation pressure is 400Kpa-800Kpa, and the impregnation time is 6-12h.

6. The method for preparing a flexible graphite bipolar plate for a fuel cell according to claim 5, characterized in that: During impregnation, the prefabricated panel is placed in a resin, a curing agent and an initiator; The resin is Heneng 994 commercial resin, the curing agent is 2,2′-azobis(2,4-dimethylvaleronitrile), the accelerator is azobisisobutyronitrile, The mass ratio of the resin, the curing agent and the initiator is 1000:2:

2.

7. The method for preparing a flexible graphite bipolar plate for a fuel cell according to claim 5, characterized in that: The cleaning and drying includes organic solvent cleaning, water bath curing and high temperature leveling; The organic solvent used in the organic solvent cleaning is one of ethanol and isopropanol, and the cleaning time is 5-30 minutes, followed by cleaning with deionized water; The water bath curing temperature is 85-95°C and the curing time is 1-4h; The steps of high temperature leveling are: first drying at a temperature of 100-150° C. for 0.5-3 hours, and then high temperature leveling at a temperature of 150-200° C. for 1-10 minutes.

8. A flexible graphite bipolar plate for a fuel cell prepared by the preparation method according to any one of claims 1 to 7.

Citation Information

Cited By

  • Method for detecting local stress of flow field area of molded plate of fuel cell

    CN122487103A